Numeracy, Multilingualism, and Supportive Leadership for Well-Being on Academic Achievement - Mai Zuniati; Suhono Suhono (Attractive : Innovative Education Journal, 2025)
This This mixed-methods study explores how numeracy literacy, multilingual literacy, and supportive leadership for well-being influence students’ academic achievement in Indonesian higher education. Motivated by low national performance in literacy and mathematics, the study used a sequential explanatory design to integrate quantitative surveys and qualitative interviews. Findings show that numeracy literacy has the most substantial effect, enhancing students’ analytical capabilities; multilingual literacy improves comprehension of diverse academic sources; and supportive leadership fosters psychological well-being and motivation. Regression analysis revealed a strong predictive model (Adjusted R² = 0.906), with all three variables showing significant impacts. Qualitative insights confirmed students' perceptions of these factors as critical for academic success. The study emphasizes the need for holistic strategies combining literacy development and emotionally supportive leadership. It concludes that empowering students with numeracy, multilingual proficiency, and psychosocially responsive leadership is vital for advancing educational outcomes in higher education